Deep-sea fungal metabolites as potential inhibitors of glucose-regulatory enzymes: In silico structure-activity analysis - Abdullah R. Alanzi; Mohammad K. Parvez; Moneerah J. Alqahtani; Mohammed S. Al-Dosari (Elsevier, 2023)
Chronic diabetes mellites related hyperglycemia is a major cause of mortality and morbidity due to further complications like retinopathy, hypertension and cardiovascular diseases. Though several synthetic anti-diabetes drugs specifically targeting glucose-metabolism enzymes are available, they have their own limitations, including adverse side-effects. Unlike other natural or marine-derived pharmacologically important molecules, deep-sea fungi metabolites still remain under-explored for their anti-diabetes potential. We performed structure-based virtual screening of deep-sea fungal compounds selected by their physiochemical properties, targeting crucial enzymes viz., α -amylase, α -glucosidase, pancreatic-lipoprotein lipase, hexokinase-II and protein tyrosine phosphatase-1B involved in glucose-metabolism pathway. Following molecular docking scores and MD simulation analyses, the selected top ten compounds for each enzyme, were subjected to pharmacokinetics prediction based on their AdmetSAR- and pharmacophore-based features. Of these, cladosporol C, tenellone F, ozazino-cyclo-(2,3-dihydroxyl-trp-tyr), penicillactam and circumdatin G were identified as potential inhibitors of α -amylase, α -glucosidase, pancreatic-lipoprotein lipase, hexokinase-II and protein tyrosine phosphatase-1B, respectively. Our in silico data therefore, warrants further experimental and pharmacological studies to validate their anti-diabetes therapeutic potential.